A ANALYSIS OF THE EFFECT OF LOCATION ON CONSUMER BEHAVIOR SHOPPING (Case study : At Grandlucky Superstore Jakarta): ANALYSIS OF THE EFFECT OF LOCATION ON CONSUMER BEHAVIOR SHOPPING (Case study : At Grandlucky Superstore Jakarta) - Yanti, Vera; Ong, Danny; Sofyanty, Devy (Advances in Social Sciences Research Journal, 2021)
This Study to determine the effect of lovation on Consumer Shopping Behaviour of Grandlucky Superstore Jakarta. The formulation of the problem in this study is whether there is an influence between the location of consumer shopping behavior at grandlucky Superstore Jakarta . The Population in this study were consumers at Grandlucky Superstore Jakarta , the determination of the number of samples using the slovin formula obtained a sample of 50 people. The variables examined in this study consisted of location factors as independent variables and consumer behaviour as dependent variables. The data used in this study were collected using a questionare that had previously been tesyed for the level of validity and reliability. Analysis of the research can be done using a linear regression formula and test the coefficient of determinant by using the help of SPSS 23 Software the result of the correlation coefficient of 0.859 indicate the relationship between location/ place against consumer behaviour. The determinant test obtained by R Square is 0.737 or 73 %of the variables of consumer behaviour are influenced by location / place variables, while remaining 27 persen is influenced by other factors.the same regression test is obtained by the regression equation Y= 7.105+0.794X, if the location/place coefficient is 0, then the consumer behaviour is 7.105 Keyword : Location/ Place, Consumer Beauviour